Cobalt-catalyzed chelation-assisted insertion of C-C multiple bonds into C(sp2)-H bonds - Yamakawa, Takeshi (2015)
In this thesis, I describe chelation-assisted cobalt-catalyzed insertion of C–C multiple bond into C(sp2)–H bond. Chapter 1 describes a brief review of a major developments of insertion of C–C multiple bond into C(sp2)–H bond. Chapter 2 describes aldimine-directed cobalt-catalyzed hydroarylation of aromatic aldimines with alkynes. The obtained ortho-alkenylated benzaldehydes are transformed into the corresponding indene and naphthalene derivatives. Chapter 3 describes annulation of -unsaturated imine and alkyne to afford 1,2-dihydropyridine under inexpensive cobalt catalysis. The reaction likely proceeds via olefinic C–H bond alkenylation followed by electrocyclization of the resulting azatriene intermediate. Chapter 4 describes cobalt-catalyzed branched-selective hydroarylation of substituted styrenes. The same catalytic system promotes isomerization of allyl, homoallyl, and bishomoallylbenzenes to the corresponding substituted styrenes and hydroarylation of the resulting -substituted styrenes to afford the corresponding 1,1-diarylalkanes.